Persepsi Konsumen Generasi Z Surabaya Tentang Pemasaran Klaim Berlebihan Pada Produk Perawatan Kulit (Studi Kasus the Originote – Retinol B3 Serum) - Wardhani, Fitra Wahyu Kusuma; Suwangsih, Iwang (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The purpose of this research is to explore more deeply information about Generation Z consumers' perceptions of overclaim on skincare products, with a specific focus on The Originote – Retinol B3 Serum among young consumers. The subjects of this research were Generation Z consumers who tend to be interested in new things promoted through on social media, which currently represents a significant market concentration. The method used was qualitative with triangulation technique, which is an approach technique that uses various methods such as interviews, documentation, and document analysis. The data analyzed came from the results of structured interviews with 10 informants who were users or the former users of the product, and were sourced from a various scientific papers. The results of the research indicate that the overclaiming on skincare products can be detrimental to many parties, including consumers tend to be afraid, distrustful, and doubtful of the products as well as manufacturers that make overclaims, which negatively impacts on its reputation. In addition, manufacturers that do not commit fraud also feel the impact, because consumers perceive that manufacturers tend to be dishonest and more focused on profit than on consumer satisfaction.